The NDF Program and the CPP Program for a People's Democratic Revolution: Umbilical Cord or Lifeline? - Rocamora, Joel (Kasarinlan: Philippine Journal of Third World Studies; Vol 8 No 4 (1993): The NDF at 20: A Front United?, 2008)
The connection between the National Democratic front (NDF) and the Communist Party of the Philippines (CPP) is no secret. It was the CPP that gave birth to the NDF in 1973. By the early 1980s however, the NDF or more accurately, the NDF Program, began to give expression to ideas that diverge from mainstream thinking within the CPP. A decade later, an attempt by a section of the CPP leadership to organize a "return to basics" has created a massive gulf between the NDF Program and the Party Program. How this happened tells a major part of the untold story of the national democratic movement. How it will be resolved will determine the future of the movement. This paper will discuss socialism and national democracy, the different NDF Programs, and international relations.